A Clinical Study on Deep Neck Infection - Shigeta, Keiichi; Kikuchi, Shigeru; Tani, Yasuhiro; Aoki, Daisuke; Yoshinami, Hiroyoshi; Takegoshi, Hideki; Ohata, Atsushi; Ohno, Toshiya (Nippon Jibi Inkoka Gakkai Kaiho, 2006)
Deep neck infection (DNI) remains an emergent and life-threatening otolaryngologic disease. We examined 69 patients, 52 men and 17 women, with DNI, who were treated in our hospital between January 1995 and December 2004. The mean age of the patients with DNI was 50.0 years and the peak incidence was in the sixth decade. Twenty patients suffered from diabetes mellitus (DM). The primary DNI lesion was found in the tonsils in 34 cases, the oral cavity in 16 cases, and the pharynx in 12 cases, respectivelys. Among the 69 patients with DNI, the infection remained in the suprahyoid region in 31 cases, but it extended to the infrahyoid region in 33 cases and to the mediastinum in 5 cases. The titer of C-reacting protein (CRP) and the duration of admission were considered as parameters of the severity of DNI. CRP was significantly higher in elderly patients, in patients with DM, and in patients whose infection extended to the infrahyoid region and to the mediastinum, however, significant difference was not found between men and women, or among the types of primary DNI lesions. Moreover, the duration of admission was significantly longer in elderly patients, in patients with DM, and in patients with infrahyoid and mediastinal DNI, whereas no significant differences were found between men and women or among the types of primary lesions. Therefore, age, DM, and the extension of DNI are considered to be important factors which determining the severity of DNI.